1975
DOI: 10.1620/tjem.116.359
|View full text |Cite
|
Sign up to set email alerts
|

Urinary kallikrein excretion and sodium metabolism in hypertensive patients.

Abstract: Urinary kallikrein excretion was measured in 21 healthy subjects and 44 patients with various types of hypertension.The kallikrein activity was determined by the method of esterolytic assay. The excretion rates in normal subjects were 112.9•}11.1 (S.E.) EU/day.The kallikrein excretion was decreased in patients with essential hypertension, the mean estimated values were 75.2•}10.0 EU/day. In this disease, however, an enhancement of urinary kallikrein was observed after sodium depletion.An obvious increase in ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 20 publications
0
25
1
Order By: Relevance
“…Nasjletti and Colina Chourio (1976) showed that mineralocorticoids increased the urinary excretion of PGE-like substances in rat, and proposed the possibility that activation of the renal kallikrein-kinin system by aldosterone promoted renal release of PGE. Our previous data (Seino et al 1975 …”
Section: Discussionmentioning
confidence: 93%
“…Nasjletti and Colina Chourio (1976) showed that mineralocorticoids increased the urinary excretion of PGE-like substances in rat, and proposed the possibility that activation of the renal kallikrein-kinin system by aldosterone promoted renal release of PGE. Our previous data (Seino et al 1975 …”
Section: Discussionmentioning
confidence: 93%
“…8 Urinary kallikrein was first reported to be subnormal in patients with essential hypertension in 1934 by Elliot and Nuzum 4 and more recently, several other groups reported similar findings. 5 …”
mentioning
confidence: 86%
“…"-" Changes in sodium chloride balance are also associated with directionally similar changes in PRA, aldosterone, and urinary kallikrein 81 "• "• 2°-ss and the infusion of angiotensin into the renal artery produces an increase in urinary kallikrein. In view of the differences between our previous work" and others, 8 "* we wished to further study urinary kallikrein in subjects with essential hypertension and normals with a careful evaluation of the known factors which influence kallikrein. We particularly wished to further characterize the relationship of urinary kallikrein to renal function, PRA, aldosterone, and sodium and potassium balance.…”
mentioning
confidence: 91%
“…Urinary and/or arterial TK can also be decreased in renovascular hypertension and genetically hypertensive rats (43,47,52,124). Although these reductions may be secondary to increases in blood pressure, decreased urinary kallikrein in (i) normotensive children of patients with essential hypertension, (ii) genetically hypertensive rats, and (iii) Dahl salt-sensitive rats that have not yet developed hypertension (48,108,159,257,278) suggests that the cause of the decrease may differ in each model.…”
Section: Kinins In Blood Pressure Regulation and The Pathogenesis Of mentioning
confidence: 99%